2004
DOI: 10.1159/000075266
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Blood Loss Underestimates Calculated Blood Loss during Radical Retropubic Prostatectomy

Abstract: Objective: To compare the calculated blood loss for radical retropubic prostatectomy (RRP) with the anesthesiologist’s and operating surgeon’s estimates of operative blood loss. Methods: A retrospective review of 52 consecutive patients undergoing RRP between January 1999 and February 2000 was performed. Patient charts were reviewed for preoperative hemoglobin (Hgbi), preoperative hematocrit (Hcti), body weight (Wt), anesthesiologist’s and surgeon’s estimated blood loss (EBLA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 16 publications
3
43
1
1
Order By: Relevance
“…Others, using different methodologies, have corroborated the finding that EBL varies with, but is typically lower than, actual surgical blood loss. 20 Moreover, there is no reason to suspect EBL should correlate better or worse with actual blood loss for one patient group rather than another (for example, for normal-weight vs overweight men). As such, though EBL may be lower than actual blood loss, the overall trends should hold.…”
Section: Discussionmentioning
confidence: 99%
“…Others, using different methodologies, have corroborated the finding that EBL varies with, but is typically lower than, actual surgical blood loss. 20 Moreover, there is no reason to suspect EBL should correlate better or worse with actual blood loss for one patient group rather than another (for example, for normal-weight vs overweight men). As such, though EBL may be lower than actual blood loss, the overall trends should hold.…”
Section: Discussionmentioning
confidence: 99%
“…USA) technology in humans), they had no basis upon which to estimate the magnitude and variance of the results they were likely to encounter. This is surprising considering that we have previously used the same technology to measure the forces applied to the maxillary incisors by videolaryngoscopes and the Macintosh laryngoscope [2,3]. We found that videolaryngoscopy results in less force applied to the maxillary incisors when compared with direct laryngoscopy, but found no difference between videolaryngoscopes.…”
Section: P Fentonmentioning
confidence: 71%
“…College We cannot agree with his suggestion that the oxygen flush is not meant to increase oxygen concentration in the inspired gas: as long ago as 1968, BS4272 [2] specifically described this feature as the emergency oxygen supply, but we agree that this is not a feature of drawover apparatus.…”
Section: P Fentonmentioning
confidence: 82%
See 1 more Smart Citation
“…This might explain the trend in performance of the EBVLoss method compared with the tool: this was poor intra-operatively (11% vs 77% of variance in measured loss explained) but improved at 24 h and significantly so at 48 h. The finding by this study that the 'estimation by expert' method outperformed the direct calculation method at 24 h is seemingly at odds with that previously reported during radical prostatectomy. A study in 52 patients used the average of pre-operative Hb and day-one postoperative Hb and demonstrated substantial underestimation by expert assessor [5]. This inconsistency might result from the inaccurately large denominator of the present study or from additional factors.…”
mentioning
confidence: 68%